Tetra-mu-acetato-kappa O-8:O `-bis{[N-(4-chlorophenyl)-4-methylpyridin-2-amine-kappa N-1]-copper(II)} - Fairuz, Z.A.; Aiyub, Z.; Abdullah, Z.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the crystal structure of the title complex, [Cu-2(CH3COO)(4)(-)( C12H11ClN2)(2)], the complete binuclear molecule is generated by a crystallographic centre of inversion; the four acetate groups each bridge a pair of Cu-II atoms. The coordination of the metal atom is distorted octahedral within a donor set defined by four O atoms, the heterocyclic N atom and the second Cu atom. The pyridine ring is twisted with respect to the benzene ring, forming a dihedral angle of 33.9 (2)degrees. An intramolecular N-H center dot center dot center dot O hydrogen bond is present between the amino group and a carboxyl O atom. Intermolecular interactions of the C-H center dot center dot center dot pi type link molecules in the crystal structure.